Green banking, bank size, operational efficiency, and financial performance: Evidence from Indonesian Stock Exchange - Eko Apriyanto; Agoestina Mappadang (AKURASI: Jurnal Riset Akuntansi dan Keuangan, 2026)
This study aims to examine the effect of green banking, bank size, and operational efficiency on the financial performance of banks listed on the Indonesia Stock Exchange (IDX) from 2021 to 2023. A quantitative approach was employed using secondary data from annual reports. The sample was selected using a saturated sampling technique, yielding 16 private and national banks with a total of 48 observations (16 banks × 3 years). Data were analyzed using multiple linear regression with SPSS. The findings reveal that, in part, green banking has no significant effect on financial performance (ROA), whereas bank size and operational efficiency (BOPO) have significant effects. Public interest statements These results provide empirical insights into the effectiveness of green banking in emerging markets and highlight the dominant role of operational efficiency within the stakeholder theory framework.